Health care costs associated with clinic visits for prevention of mother-to-child transmission of HIV in Dar es Salaam, Tanzania - Naburi, Helga; Mujinja, Phares; Kilewo, Charles; Biberfeld, Gunnel; Bärnighausen, Till; Manji, Karim; Lyatuu, Goodluck; Urrio, Roseline; Zethraeus, Niklas; Orsini, Nicola; Ekström, Anna Mia (Medicine, 2021)
Early and appropriate antenatal care (ANC) is key for the effectiveness of prevention of mother-to-child transmission (PMTCT) of human immunodeficiency virus (HIV). We evaluated the importance of ANC visits and related service costs for women receiving option B+ to prevent mother-to-child transmission (MTCT) of HIV in Tanzania. - A cost analysis from a health care sector perspective was conducted using routine data of 2224 pregnant women newly diagnosed with HIV who gave birth between August 2014 and May 2016 in Dar es Salaam, Tanzania. We evaluated risk of infant HIV infection at 12 weeks postnatally in relation to ANC visits (<4 vs ≥4 visits). Costs for service utilisation were estimated through empirical observations and the World Health Organisation Global Price Reporting Mechanism. - Mean gestational age at first ANC visit was 22 (±7) weeks. The average number of ANC/prevention of MTCT visits among the 2224 pregnant women in our sample was 3.6 (95% confidence interval [CI] 3.6-3.7), and 57.3% made ≥4 visits. At 12 weeks postnatally, 2.7% (95% CI 2.2-3.6) of HIV exposed infants had been infected. The risk of MTCT decreased with the number of ANC visits: 4.8% (95% CI 3.6-6.4) if the mother had <4 visits, and 1.0% (95% CI 0.5-1.7) at ≥4. The adjusted MTCT rates decreased by 51% (odds ratio 0.49, 95% CI 0.31-0.77) for each additional ANC visit made. The potential cost-saving was 2.2 US$ per woman at ≥4 visits (84.8 US$) compared to <4 visits (87.0 US$), mainly due to less defaulter tracing. - Most pregnant women living with HIV in Dar es Salaam initiated ANC late and >40% failed to adhere to the recommended minimum of 4 visits. Improved ANC attendance would likely lead to fewer HIV-infected infants and reduce both short and long-term health care costs due to less spending on defaulter tracing and future treatment costs for the children.